Biological Evaluations, NMR Analyses, Molecular Modeling Studies, and Overview of the Synthesis of the Marine Natural Product (−)-Mucosin - Jens M. J. Nolsøe; Jarl Underhaug; Åshild Moi Sørskar; Simen Gjelseth Antonsen; Karl E. Malterud; Osman Gani; Qiong Fan; Marit Hjorth; Thomas Sæther; Trond V. Hansen; Yngve H. Stenstrøm (Molecules, 2024)
Natural products obtained from marine organisms continue to be a rich source of novel structural architecture and of importance in drug discovery, medicine, and health. However, the success of such endeavors depends on the exact structural elucidation and access to sufficient material, often by stereoselective total synthesis, of the isolated natural product of interest. (−)-Mucosin (1), a fatty acid derivative, previously presumed to contain a rare cis-bicyclo[4.3.0]non-3-ene moiety, has since been shown to be the trans-congener. Analytically, the fused bicyclic ring system in (−)-1 constitutes a particular challenge in order to establish its relative and absolute stereochemistry. Herein, data from biological evaluations, NMR and molecular modeling studies of (−)-1 are presented. An overview of the synthetic strategies enabling the exact structural elucidation of (−)-mucosin (1) is also presented.